Formation of cracker quality indicators using non-traditional raw materials - L. Z. Borieva; F. A. Bischokova; I. B. Shogenova (Новые технологии)
The ability to model the formula and assortment of flour confectionery is the main advantage of this group of products in the production process. The article presents the results of the research on the effect of pumpkin puree on the quality of white wheat flour crackers. Pumpkin puree contains vitamin T, which is considered to be a vitamin-like substance, also known as vitamin B11, but its most famous name is carnitine, and it is usually referred to as a fat burner. Carnitine has antioxidant properties. Pumpkin puree contains macroand micronutrients of magnesium, sulfur, chlorine, copper, zinc, which are practically not present in ready-made crackers, and the content of potassium and calcium in pumpkin puree is almost twice as much as in crackers.  During the baking process in the laboratory, pumpkin puree was added to the cracker dough in the amount of 5;10;15;20;25 % of the flour.  The dough was prepared in a two-phase way. Pumpkin puree contributed to increased plastic deformation of the dough, increased the rate of relaxation of the internal stresses of the dough when rolling out and forming dough pieces. Cracker dough with the addition of 15% puree had optimal properties for getting the best quality crackers.